PS-BPB05-8: POSSIBLE INTERACTION OF ANGIOTENSIN II TYPE 1 RECEPTOR-ASSOCIATED PROTEIN WITH TRANSFERRIN RECEPTOR-1 VIA MODULATION OF THE RECEPTOR INTERNALIZATION. (January 2023) - Abe, Eriko; Yamashita, Akio; Hirota, Keigo; Yamaji, Takahiro; Urate, Shingo; Suzuki, Toru; Tanaka, Shohei; Tsukamoto, Shunichiro; Taguchi, Shinya; Azushima, Kengo; Wakui, Hiromichi; Takahashi, Hidehisa; et al.
Abstract : Objective: Angiotensin II type 1 receptor (AT1R)-associated protein (ATRAP) was originally identified as a specific binding protein of AT1R. We have shown that ATRAP promotes constitutive internalization of AT1R so as to inhibit the pathological activation of its downstream signaling. Also, we reported that genetic knockdown of ATRAP exacerbates kidney fibrosis in mice along with functional mitochondrial abnormalities and subsequent increases in ROS production. These effects of ATRAP on kidney fibrosis were suggested to be AT1R-independent actions, but the molecular mechanism is unclear. The present study was designed to explore a novel interacting protein of ATRAP that was involved in the mechanism by which ATRAP protected against kidney fibrosis, independent of the interaction with AT1R. Design and method: We established Human Embryonic Kidney 293 cells which were able to induce the expression of Flag-tagged ATRAP (HEK293_Flag-ATRAP cells) in a doxycycline-dependent manner. After immunoprecipitation with anti-Flag antibodies, the Flag-ATRAP complex was analyzed with a mass spectrometer. Among identified proteins, we focused on transferrin receptor1(TfR1). To confirm the molecular interaction, co-immunoprecipitation was performed using anti-Flag or anti-TfR1 antibodies. Additionally, to validate functional interactions, we analyzed intracellular iron concentrations using fluorescent probe of ferric iron. Furthermore, we verified the TfR1 expression in two ways. First, immunofluorescence staining of TfR1 in the whole cell or on the cell surface only. Second, Western blot with whole cell lysate treated with ferristatin II which degraded TfR1 on the cell surface. Results: On the mass spectrometric analysis, 377 proteins were identified as the ATRAP binding protein candidates. Enrichment analysis indicated that proteins related to endocytosis and vesicle trafficking were enriched. TfR1 is also identified. We confirmed the molecular interaction between ATRAP and TfR1 by co-immunoprecipitation. Enhanced ATRAP expression decreased the cellular iron level as well as the expression of TfR1 on the cell surface, despite no evident change in whole cell. Furthermore, we showed that ATRAP suppressed the effect of ferristatin II. Conclusion: We propose a molecular and functional link between ATRAP and TfR1. ATRAP would regulate TfR1 availability via downregulation of cell surface TfR1 via promotion of its internalization. TfR1 promotes intracellular localization of the ferric iron-bound transferrin. Iron is a key factor in the process of kidney fibrosis via production of ROS in relation to deterioration of mitochondrial function. Taken together, this novel ATRAP-TfR1 axis might be the mechanism relevant to the ROS/mitochondrial dysfunction-mediated process of kidney fibrosis.